العوامل المؤدية الى تفشي ظاهرة العنف لدى طلبة المرحلة الثانوية من وجهة نظر الطلبة - غوادرة, نضال (Université de M'sila, 2016)
هدف البحث الى معرفة العوامل المؤدية الى تفشي ظاهرة العنف لدى طلبة المرحلة الثانوية بمحافظة الخليل من وجهة نظر الطلبة، تأ لفت عينة البحث من 349 طالباً وطالبة من طلبة المدارس الحكومية التابعة لمديرية تربية وتعليم الخليل، اختيرت بالطريقة العشوائية الطبقية، تم اعداد اس تبيان لجمع البيانات وتم التحقق من صدقه وثباته . و أسفرت النتائج الى عدم وجود فروق في ظاهرة العنف تعزى لكل من متغير )الجنس، والتخصص( وتوجد فروق بين طلاب القرى وطلاب المدينة لصالح طلاب المدينة وبين طلبة المدينة وطلبة المجيمات لصالح طلبة المجيمات، في حين أنه لا توجد فروق في ظاهرة العنف في المدارس الثانوية تعزى لمتغير المس توى ال كاديمي، وفي ضوء ذلك تم طرح بعض التوصيات The study aims at investigating the factors leading to the spread of violence phenomena among Palestinian secondary school student at Hebron region. The random stratified sample consisted of 349 male and female students in the schools of Hebron Directorate of Education. The questionnaire was based the researchers assured its reliability and validity following the scientific procedures. Result showed that there were no statisticlly significant differences in violence phenomena at secondary schools attributed to gender and academic stream. there were statistically significant differences between students from villages and those from city for the favor of those from the city and between the city camp for the favor of students from the camp .there were no statistically significant differences in violence phenomena at secondary schools attributed to qualification. Recommendations were
Keywords: ظاهرة العنف، المرحلة الثانوية، محافظة الخليل